A probe sterile coupling agent patch capable of improving the clarity of ultrasound images

By using hydrogel patches with high CMCS and PAAs content on the ultrasound probe, the problem of coupling agent loss during sterile invasive operations is solved, the ultrasound image quality is improved, the operation process is simplified and the risk of infection is reduced.

CN119055801BActive Publication Date: 2025-02-25PEKING UNIVERSITY THIRD HOSPITAL (THE THIRD CLINICAL MEDICAL SCHOOL OF PEKING UNIVERSITY) +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411557100.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Prior Art In sterile and invasive operations, the coupling agent between the ultrasonic probe and the skin is easily lost, resulting in a decrease in the quality of the ultrasonic image and the inability to further add the coupling agent, extending the operating time and increasing the risk of infection.

Method used

Using a hydrogel patch including carboxymethyl chitosan (CMCS), sodium polyacrylate (PAAs), silica (SiO2) and gallium nitrate (GaNO3) is directly adhered to the ultrasound probe to improve ultrasound Imaging effect and ensuring sterility.

Benefits of technology

The hydrogel patch has super strong adhesion, which can improve the clarity of ultrasound images, reduce operating time, reduce infection risk, and extend the service life of the ultrasound probe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119055801B_ABST
    Figure CN119055801B_ABST
Patent Text Reader

Abstract

The present invention discloses a probe sterile coupling agent patch that can improve the clarity of ultrasonic images and a preparation method thereof. The probe sterile coupling agent patch that can improve the clarity of ultrasonic images includes the following components by weight: 0.2-0.8 parts of carboxymethyl chitosan, 1-1.5 parts of sodium polyacrylate, 0.05 parts of silicon dioxide, 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water. The sterile coupling agent patch of the present application is simple in design and easy to use, and can be applied to various types of ultrasonic probes, with low cost and high utilization rate; it can eliminate the need to add coupling agent during operation, make the coupling agent layer more homogeneous, improve the imaging effect, reduce the ultrasonic preparation time, and reduce the loss of the ultrasonic probe; at the same time, it can shorten the operation time, reduce the operation trauma, improve the success rate of invasive operation, improve the anesthesia and analgesia effect, reduce the infection rate and anesthesia complications, extend the service life of ultrasound, benefit patients, and reduce the consumption of medical resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical technology, and in particular to a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images. Background Art

[0002] In clinical anesthesia, the number of sterile invasive operations under B-ultrasound guidance is huge. B-ultrasound coupling agent is an essential auxiliary material for invasive operations under B-ultrasound. It is composed of water-soluble polymer materials and is applied to the patient's invasive operation site to fill the tiny gap between the ultrasound probe and the skin to obtain clear ultrasound images and play a certain lubricating role.

[0003] In sterile invasive operations, the process of preparing a sterile ultrasound probe is complicated. It is necessary to apply a B-ultrasound coupling agent to the front end of the ultrasound probe, and use a sterile film or a sleeve to wrap the ultrasound probe to achieve probe sterility. Then, apply a sterile coupling agent to the operation site, and then wear sterile gloves to hold the sterile prepared probe for B-ultrasound scanning. This process is complicated and time-consuming. The coupling agent in the sterile film is very easy to lose, causing the quality of the ultrasound image to deteriorate, and it is impossible to further add coupling agent, which significantly prolongs the operation time and affects the operation effect. In addition, during invasive operations, coupling agent must be applied to the invasive operation site, and multiple uses of coupling agent are difficult to ensure sterility, which can easily cause infection in the patient's invasive operation site. Therefore, sterile consumables that can improve the imaging ability of B-ultrasound probes have broad application prospects and markets. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a probe sterile coupling agent patch that can improve the clarity of ultrasound images. The CMCS and PAAs in the hydrogel patch contain a large number of carboxyl groups, which make it have super strong adhesion. The sterile coupling agent patch can be directly adhered to the ultrasound probe and used directly to improve the ultrasound imaging effect.

[0005] The technical problem to be solved by the present invention is achieved through the following technical solutions:

[0006] A probe sterile coupling agent patch capable of improving the clarity of ultrasonic images comprises the following components in parts by weight: 0.2-0.8 parts of carboxymethyl chitosan (CMCS), 1-1.5 parts of sodium polyacrylate (PAAs), 0.05 parts of silicon dioxide (SiO2), 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water.

[0007] Preferably, the above technical solution includes the following components in parts by weight: 0.8 parts of carboxymethyl chitosan (CMCS), 1.5 parts of sodium polyacrylate (PAAs), 0.05 parts of silicon dioxide (SiO2), 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water.

[0008] A method for preparing a probe sterile coupling agent patch capable of improving the clarity of an ultrasonic image comprises the following steps:

[0009] (1) Preparation of chitosan aqueous solution: Weigh a certain amount of carboxymethyl chitosan (CMCS) to prepare chitosan aqueous solution, sterilize it under high pressure, and place it on a clean bench to cool to room temperature for later use;

[0010] (2) Preparation of a gallium nitrate-silicon dioxide mixed solution: Weigh a certain amount of gallium nitrate, dissolve it in deionized water, filter it through a 0.22 μm filter head, and then mix it with sterile silicon dioxide (SiO2) to obtain a gallium nitrate-silicon dioxide mixed solution;

[0011] (3) Mixing: Add the gallium nitrate-silicon dioxide mixed solution dropwise into a beaker containing a sterile chitosan aqueous solution, stir magnetically until the three are fully mixed, then add a certain amount of sterile sodium polyacrylate (PAAs) into the solution and stir evenly to obtain a mixed solution;

[0012] (4) Curing and molding: The mixed liquid is injected into a polytetrafluoroethylene mold and allowed to stand and solidify to obtain the CMCS / PAAs hydrogel.

[0013] Preferably, in the above technical solution, in step (1), the high pressure sterilization is sterilization at 0.1 MPa and 121°C for 15 min.

[0014] Preferably, in the above technical solution, in step (2), the ratio of silicon dioxide to gallium nitrate solution is 1:10 (g / mL); and the concentration of gallium nitrate solution is 0.05% (g / mL).

[0015] Preferably, in the above technical solution, in step (3), the magnetic stirring process is: using a magnetic stirrer to make the magnetic rotor rotate at a constant speed to avoid splashing of the liquid in the beaker.

[0016] Preferably, in the above technical solution, in the CMCS / PAAs obtained in step (4), the mass ratio of CMCS to PAAs is (0.2-0.8):(1-2).

[0017] Preferably, in the above technical solution, in the CMCS / PAAs obtained in step (4), the mass ratio of CMCS to PAAs is 0.8:1.5.

[0018] The invention discloses an application of a probe sterile coupling agent sticker capable of improving the clarity of ultrasonic images in sterile invasive surgery under ultrasound guidance.

[0019] Preferably, in the above technical solution, the application is knee replacement under spinal anesthesia.

[0020] The above technical solution of the present invention has the following beneficial effects:

[0021] The sterile coupling agent patch of the present application is a disposable sterile design, suitable for various types of sterile invasive operations under ultrasound guidance. The design is simple and easy to use, and can be applied to various types of ultrasound probes, with low cost and high utilization rate. It can eliminate the need to add coupling agent during the operation, make the coupling agent layer more homogeneous, improve the imaging effect, reduce ultrasound preparation time, and reduce ultrasound probe loss.

[0022] The sterile coupling agent patch of the present application can shorten the operation time, reduce the operation trauma, improve the success rate of invasive operation, improve the anesthesia and analgesia effect, reduce the infection rate and anesthesia complications, extend the service life of ultrasound, benefit patients, and reduce the consumption of medical resources.

[0023] In the present application, since the CMCS and PAAs in the hydrogel patch contain a large number of carboxyl groups, the patch has super strong adhesion. The sterile coupling agent patch can be directly attached to the ultrasound probe for direct use to improve the ultrasound imaging effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0025] Figure 1 This is a graph showing the changes in mechanical properties of hydrogels with different carboxymethyl chitosan (CMCS) contents.

[0026] Figure 2 Stress-strain diagram of hydrogels with different CMCS contents.

[0027] Figure 3 This is a graph showing the changes in mechanical properties of hydrogels with different PAAs contents.

[0028] Figure 4 Stress-strain diagram of hydrogels with different PAAs contents.

[0029] Figure 5 This is a diagram showing the changes in mechanical properties of CMCS0.8 PAAs1.5 hydrogel after fracture and self-repair.

[0030] Figure 6 This is the stress-strain diagram of CMCS0.8PAAs1.5 hydrogel after self-repair.

[0031] Figure 7 This is a graph showing the acoustic attenuation changes of the hydrogel patch with and without SiO2.

[0032] Figure 8 Ultrasound test images of the brachial plexus and internal jugular vein in the hydrogel group and the medical coupling agent group. DETAILED DESCRIPTION

[0033] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0034] The applicant's hydrogel ultrasound probe coupling agent patch, which can improve the clarity of ultrasound images, is a disposable sterile consumable designed for invasive operations under clinical B-ultrasound. It is a solid coupling agent that has good ultrasound image imaging ability and probe adhesion after gelation, and is sterilely prepared. It is wrapped in the ultrasound probe for one-time use and then used in contact with the patient's skin, and is easy to remove when exposed to water. It can eliminate the need to add liquid coupling agent during the operation, making the coupling agent layer more homogeneous, improving the imaging effect and improving the sterility of the invasive operation area. The transformation application of this application is expected to help improve doctors' ultrasound application capabilities, reduce ultrasound sterile preparation time, increase the success rate of invasive operations, reduce the incidence of infection at the puncture site, improve medical safety, and provide patients with better medical services.

[0035] Examples 1-6

[0036] A probe sterile coupling agent patch capable of improving the clarity of ultrasonic images comprises the following components in parts by weight: 0.2-0.8 parts of carboxymethyl chitosan (CMCS), 1-1.5 parts of sodium polyacrylate (PAAs), 0.05 parts of silicon dioxide (SiO2), 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water.

[0037] The method for preparing the above-mentioned probe sterile coupling agent patch comprises the following steps:

[0038] (1) Preparation of chitosan aqueous solution: Weigh a certain amount of carboxymethyl chitosan (CMCS) to prepare chitosan aqueous solution, sterilize under high pressure (0.1 MPa, 121°C for 15 min), and place in a clean bench to cool to room temperature for use;

[0039] (2) Preparation of a gallium nitrate-silicon dioxide mixed solution: Weigh a certain amount of gallium nitrate, dissolve it in deionized water, filter it through a 0.22 μm filter head, and then mix it thoroughly with sterile silicon dioxide (SiO2) to obtain a gallium nitrate-silicon dioxide mixed solution; wherein the ratio of silicon dioxide to gallium nitrate solution is 1:10 (g / mL); and the concentration of the gallium nitrate solution is 0.05% (g / mL).

[0040] (3) Mixing: Add the gallium nitrate-silicon dioxide mixed solution dropwise into a beaker containing a sterile chitosan aqueous solution, stir magnetically (using a magnetic stirrer to rotate the magnetic rotor at a constant speed to avoid splashing of the liquid in the beaker) until the three are fully mixed, then add a certain amount of sterile sodium polyacrylate (PAAs) into the solution and stir evenly to obtain a mixed solution;

[0041] (4) Curing and molding: The mixed liquid is injected into a polytetrafluoroethylene mold and allowed to stand for curing to obtain CMCSx / PAAsy hydrogel, where x represents the mass of CMCS (g) and y represents the mass of PAAs (g).

[0042] In the CMCS / PAAs obtained in step (4), the mass ratio of CMCS to PAAs is (0.2-0.8):(1-2). The specific details are shown in Table 1:

[0043]

[0044] The performance tests of the patches of Examples 1-6 were performed:

[0045] (1) Tensile properties of ultrasonic coupling agent patch materials:

[0046] In order to explore whether the addition of CMCS and PAAs can enhance the mechanical properties and the effect of changes in content on the hydrogel system, tensile tests were performed. After preliminary experiments, the feasibility of preparing hydrogels was determined. CMCS and PAAs hydrogen bonded to construct the internal network structure of the hydrogel, and then bonded with Ga 3+ Metal ion complexation occurs, enhancing the mechanical properties of the hydrogel system.

[0047] In order to determine the ratio of the hydrogel, the amount of PAAs was set to 1.5 g, and the effect of the change in CMCS content on the mechanical properties of the hydrogel was tested. Figure 2 As shown in the figure, as the CMCS content increases, the fracture strength also increases, which confirms that the addition of CMCS can improve the mechanical properties of the hydrogel. When the amount of CMCS reaches 0.8 g, the mechanical strength reaches the highest. By adjusting the content of CMCS and PAAs, CMCS0.8PAAs1.5 hydrogel was obtained, and its maximum tensile strength and strain reached 146.51 kPa and 2305%, respectively. The experimental results show that the introduction of CMCS and PAAs into the hydrogel system improves the mechanical properties of the hydrogel.

[0048] At the same time, with the increase of CMCS content, the stress-strain effect of the hydrogel continues to improve.

[0049] The amount of CMCS was fixed, and different PAAs were added to prepare hydrogels. As shown in Figure 3, with the increase of PAAs content, the fracture strength of the hydrogel first increased and then decreased. This is because the degree of cross-linking of the hydrogel becomes more and more dense with the increase of content, and when the content is too high, it causes excessive cross-linking, making the hydrogel brittle and prone to fracture, reducing the mechanical properties of the hydrogel. At the same time, the stress strain of the hydrogel decreases, as shown in Figure 4.

[0050] (2) Self-healing properties of ultrasonic coupling agent patch materials

[0051] The strength of the self-healing property is the basis for measuring whether the ultrasonic coupling agent patch can withstand repeated needle punctures and self-repair. The hydrogel strips obtained by cutting the fracture surfaces of the hydrogel and letting them stand in contact with each other were re-tested by a tensile machine to measure the self-healing property of the hydrogel. The tensile results of the hydrogel patch are shown in Figures 5 and 6. The hydrogel still has good self-healing properties after self-healing. The hydrogel that was not cut off was regarded as a non-self-healing hydrogel as a positive control. Compared with the hydrogel that was self-healed, the mechanical properties of the hydrogel decreased, but it still had good tensile properties and stress-strain capacity. There was no significant difference in elongation compared with that of the non-self-healing. This is due to the coordination of the intermolecular forces between carboxymethyl chitosan and sodium polyacrylate in the ultrasonic coupling agent patch and the hydrogen bonds between the hydrogel networks, which gave the hydrogel additional self-healing properties.

[0052] (3) Adhesion of ultrasonic coupling agent patch material

[0053] The adhesion of the ultrasonic coupling agent patch to different substrates shows that it has good adhesion to PS, PP, glass, rubber, metal, ceramics and pig skin.

[0054] The ultrasound coupling agent patch has excellent adhesion properties to different surfaces, which ensures good adhesion stability and defect filling when applied to the surface of the ultrasound probe. When the adhered hydrogel meets water, it can be quickly removed and is degradable and pollution-free, which provides convenience for its clinical application.

[0055] (4) Acoustic properties of ultrasonic coupling agent patch materials

[0056] As the content of carboxymethyl chitosan in the sterile coupling agent patch increases, the acoustic velocity of the patch increases. The results are shown in Table 2 below.

[0057]

[0058] In addition, the sound velocity of the hydrogel patch containing silica is significantly higher than that of the hydrogel patch without silica, as shown in Table 3. The slope of its acoustic attenuation coefficient is greater than that of the hydrogel patch without silica ( Figure 7). This is because the CMCS0.6 / PAAs1.5 hydrogel patch has an interpenetrating cross-linked network structure, and the gel has many microphase interfaces. The existence of these interfaces makes the energy in the sound easily lost due to scattering and refraction during the propagation process, but its sound speed is still higher than the transmission of commercial ultrasonic coupling agents. After the introduction of silica, the linear correlation coefficient of the hydrogel patch reached 0.98, with a high degree of linearity. This is due to the interaction between the polymers in the hydrogel. After the metal silicon oxide ions fill the hydrogel network, the sound conduction rate of the hydrogel patch is improved.

[0059]

[0060] (5) Ultrasonic imaging function of ultrasonic coupling agent patch materials

[0061] By comparing different ultrasonic coupling agent components, three common solid coupling agent materials were selected as the substrate membrane, namely polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP) and the hydrogel in this study. Comprehensive judgments were made based on the material sound velocity, acoustic impedance, flexibility, and ultrasonic image clarity. It is currently believed that CMCS / PAAs hydrogel has its superiority as the substrate of ultrasonic coupling agent. The results are shown in Table 4.

[0062]

[0063] Clinical anesthesiologists compared CMCS / PAAs hydrogel with commonly used ultrasound coupling agents in the clinic and believed that CMCS / PAAs hydrogel was superior in terms of flexibility and ultrasound image clarity as an ultrasound coupling agent. The results are shown in Figure 8.

[0064] Depend on Figure 8 The results of in vitro ultrasound imaging show that the depth and clarity of the hydrogel group when observing the brachial plexus and internal jugular vein nerves are significantly higher than those of ordinary medical ultrasound coupling agents. This is consistent with the above-mentioned results that its ultrasound velocity is significantly higher than that of medical coupling agents. This is mainly attributed to the stability of the hydrogel and its excellent acoustic attenuation performance close to that of human tissue.

[0065] Application Example 1

[0066] This study was a single-center, randomized, single-blind design. A total of 200 patients who underwent elective knee replacement under spinal anesthesia were selected, and continuous femoral nerve block was used as a postoperative analgesia method. After the operation, the patient was in a supine position, and a portable ultrasound device (British SONATEST SiteScan 240) and an ultrasonic high-frequency probe were used to scan the patient's target femoral nerve. The ultrasound coupling agent group used the coupling agent patch for probe preparation, and the traditional coupling agent group used the current routine sterile probe preparation method in our department for probe preparation. There was no statistical difference in the general condition of the two groups of patients.

[0067] (1) B-ultrasound preparation time (min), operation time (min), and number of puncture attempts before successful operation

[0068] The results showed that in the ultrasound coupling agent group (100 cases), the average ultrasound preparation time was about 5.1±1.2 min, the average operation time was about 4.9±0.7 min, and the average number of puncture attempts was about 1.6±0.4 times; in the traditional coupling agent group (100 cases), the ultrasound preparation time was about 7±1.6 min, the operation time was about 5.8±0.5 min, and the number of puncture attempts was 2.2±0.7 times.

[0069] (2) Patient satisfaction and anesthesiologist satisfaction scores (maximum 100 points)

[0070] The results showed that the average patient satisfaction in the ultrasound coupling patch group (100 cases) was 95±4.6, and the doctor satisfaction was 95.9±5.5; the average patient satisfaction in the ultrasound coupling patch group (100 cases) was 90±7.5, and the doctor satisfaction was 92.4±4.8.

[0071] (3) Pain severity in the two groups (12h, 24h, and 48h after surgery; VAS score was used to evaluate postoperative pain)

[0072] The results showed that the VAS scores of the ultrasonic coupling agent group (100 cases) were 3.3±0.7, 2.9±0.7, and 2.6±0.4 at 12, 24, and 48 hours after surgery, respectively; the VAS scores of the traditional coupling agent group (100 cases) were 4±0.6, 3.4±0.5, and 2.4±0.7 at 12, 24, and 48 hours after surgery, respectively.

[0073] (4) Comparison of C-RCSQ sleep quality scores between the two groups (mean ± standard deviation)

[0074] The results showed that the average values ​​of the day before surgery, the day of surgery, the first day after surgery, and the second day after surgery in the ultrasound coupling agent group (100 cases) were 83.1±8.4, 49.4±7.9, 64.6±6.5, and 70.2±7.0, respectively; the average values ​​of the day before surgery, the day of surgery, the first day after surgery, and the second day after surgery in the traditional coupling agent group (100 cases) were 81.0±7.8, 44.6±8.8, 62.3±6.1, and 71.6.2±8.3, respectively.

[0075] In summary, by comparing the ultrasonic coupling agent group with the traditional coupling agent group, we can draw the following conclusions:

[0076] 1. Operation efficiency: The ultrasound coupling agent group was superior to the traditional coupling agent group in B-ultrasound preparation time, operation time and number of puncture attempts. This shows that the use of ultrasound coupling agent can improve the efficiency of the operation and reduce the number of puncture attempts, thereby potentially reducing the pain and discomfort of patients.

[0077] 2. Patient satisfaction and doctor satisfaction: The patient satisfaction and doctor satisfaction scores of the ultrasound coupling agent group were higher than those of the traditional coupling agent group. This shows that the use of the ultrasound coupling agent patch not only improves patient satisfaction, but also is recognized by doctors. The reason may be that this method simplifies the operation process, reduces the difficulty of operation, and improves the success rate.

[0078] 3. Pain control: The VAS scores of the ultrasound coupling agent group at 12 hours, 24 hours and 48 hours after surgery were lower than those of the traditional coupling agent group, showing better pain control effects. This is of great significance for improving the comfort of patients after surgery and accelerating the recovery process.

[0079] 4. Sleep quality: The C-RCSQ sleep quality scores of the ultrasound coupling agent group on the day before surgery, the day of surgery, the first day after surgery, and the second day after surgery were better than those of the traditional coupling agent group. Good sleep quality is crucial for the recovery of postoperative patients and promotes the recovery speed of patients.

[0080] Therefore, ultrasound coupling patch can be used as one of the effective methods to improve postoperative analgesia, and it is worthy of further promotion and application in clinical practice.

[0081] Although the present invention has been disclosed as above by the embodiments, it is not intended to limit the present invention. Any person skilled in the art may make various choices and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is limited by the claims and their equivalents.

Claims

1. A probe sterile coupling agent patch capable of improving the clarity of ultrasonic images, characterized in that: The invention comprises the following components in parts by weight: 0.2-0.8 parts of carboxymethyl chitosan (CMCS), 1-1.5 parts of sodium polyacrylate (PAAs), 0.05 parts of silicon dioxide (SiO2), 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water (H2O).

2. The probe sterile coupling agent patch for improving the clarity of ultrasonic images according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 0.8 parts of carboxymethyl chitosan (CMCS), 1.5 parts of sodium polyacrylate (PAAs), 0.05 parts of silicon dioxide (SiO2), 0.005 parts of gallium nitrate (GaNO3), and 10 parts of deionized water.

3. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to any one of claims 1-2, characterized in that: The following steps are involved: (1) Preparation of chitosan aqueous solution: weigh a certain amount of carboxymethyl chitosan (CMCS) to prepare chitosan aqueous solution, sterilize it by high pressure, and place it in a clean bench to cool to room temperature for use; (2) preparing a gallium nitrate-silicon dioxide mixed solution: weighing a certain amount of gallium nitrate, dissolving it in deionized water, filtering it through a 0.22 μm filter head, and fully mixing it with sterile silicon dioxide (SiO2) to obtain a gallium nitrate-silicon dioxide mixed solution; (3) Mixing: Add the gallium nitrate-silicon dioxide mixed solution dropwise into a beaker containing a sterile chitosan aqueous solution, stir magnetically until the three are fully mixed, then add a certain amount of sterile sodium polyacrylate (PAAs) into the solution, stir evenly, and obtain a mixed solution; (4) Curing and molding: The mixed solution is injected into a polytetrafluoroethylene mold and allowed to stand and solidify to obtain the CMCS / PAAs hydrogel.

4. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to claim 3, characterized in that: In step (1), high pressure sterilization is sterilization at 0.1 MPa and 121° C. for 15 min.

5. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to claim 3, characterized in that: In step (2), the ratio of silicon dioxide to gallium nitrate solution is 1:10; the concentration of gallium nitrate solution is 0.05%.

6. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to claim 3, characterized in that: In step (3), the magnetic stirring process is: using a magnetic stirrer to rotate the magnetic rotor at a constant speed to prevent splashing of the liquid in the beaker.

7. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to claim 3, characterized in that: In the CMCS / PAAs obtained in step (4), the mass ratio of CMCS to PAAs is (0.2-0.8):(1-1.5).

8. The method for preparing a probe sterile coupling agent patch capable of improving the clarity of ultrasonic images according to claim 3, characterized in that: In the CMCS / PAAs obtained in step (4), the mass ratio of CMCS to PAAs is 0.8:1.5.

Citation Information

Patent Citations

  • Injectable hydrogel as well as preparation method and application thereof

    CN113416326A

  • Dual-network hydrogel and preparation method thereof

    CN113599579A